PENGEMBANGAN MODEL LATIHAN TENDANGAN SABIT BERBASIS VIDEO DALAM PENCAK SILAT PADA SISWA EKSTRAKURIKULER PENCAK SILAT MAN 1 BANDAR LAMPUNG - Sulistianta, Heru; Hata, Fikri Alfakih; Rifaldo, Muhammad Fajril; Siswoyo, Joan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a video-based crescent kick training model for students in the pencak silat extracurricular program at MAN 1 Bandar Lampung and to determine the feasibility of the product. The research used the ADDIE development model consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted at MAN 1 Bandar Lampung, using interviews, observations, and questionnaires for data collection. Interviews and observations identified problems, while questionnaires were used to assess product feasibility. The result is an e-learning instructional material based on Google Sites for pencak silat learning. The product was considered feasible based on validation by material experts (85%), language experts (82.5%), media experts (87.5%), physical education teachers (100%), small-scale trials (96%), and large-scale trials (97%). Revisions included adding learning objectives at the beginning of the video. Overall, the product is categorized as highly feasible and suitable for use in pencak silat extracurricular training at MAN 1 Bandar Lampung.